Upaya Peningkatan Motivasi dan Prestasi Belajar Peserta Didik melalui Penerapan Problem Based Learning dalam Proses Pembelajaran Pendidikan Agama Katolik pada Peserta Didik Kelas VII SMP Negeri 4 Ulunoyo - Yeremia Giawa (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Students' motivation and learning achievement are one of the indicators of the success or failure of the implementation of the learning process in schools. To get maximum motivation and learning achievement of students, various efforts are made such as improving the curriculum which gives rise to various new learning models in the learning process such as Problem Based Learning (PBL) learning models, Inquri, Project Based Learning and so on. This study aims to determine the influence of the application of the Problem Based Learning learning model on increasing student motivation and learning achievement. This study uses a quantitative approach. The subject of this study is 12 students in grade VII of SMP Negeri 4 Ulunoyo who are Catholic. This research was carried out at SMP Negeri 4 Ulunoyo, Ulunoyo District, South Nias Regency, North Sumatra Province. The implementation of this research was carried out in two cycles with different learning materials. The results of this study show that the application of the Problem Based Learning learning model in the learning process of Catholic Religious Education subjects both in the implementation of cycle I and cycle II can increase the motivation and learning achievement of grade VII students of SMP Negeri 4 Ulunoyo with the percentage in each cycle being cycle I of 66.65% and cycle II of 90, 62%.